Contemporary digital qualitative research in sport, exercise and health: introduction. Issue 1 (2nd January 2021) - Goodyear, Victoria; Bundon, Andrea
ABSTRACT: This paper provides an introduction to the Special Issue on Digital Qualitative Research in Sport, Exercise and Health. The aim is to spur qualitative researchers to new ways of thinking, new ways of doing, and new ways of representing with the ultimate goal of supporting new ways of knowing, through the lens of digital technologies. First, digital qualitative research is defined and articulated as research that engages in qualitative inquiry and meaning making through digital content, digital contexts and/or digital practices. In using this definition, an analysis of the articles published in sport, exercise and health reveal that most research to date has primarily focused on technology as method, the impacts of technologies on participants, technology as an empirical finding, and/or technology as a medium to represent research findings. Accordingly, and with the intent of advancing digital qualitative research in sport, exercise and health, the concept of practice architectures is used as a heuristic device to articulate the cultural, social and material conditions that potentially support or constrain current and potential future research. Embedded in this discussion, is an overview of the papers in this Special Issue. Overall, these papers showcase the most innovative and world-leading digital qualitative research in sport, exercise and health to date, and provide inspiration and direction for moving forward. The papers use established qualitative concepts, theories and methodologies, offer challenges to existing frameworks, and illustrate contemporary understandings of sport, exercise and health through digital mediums.